Penggunaan Pseudosa japonica (Bambu Jepang) sebagai Sound Barrier Alami di Markas Militer Komando Pasukan Khusus - Aziz Faza Hargiyanto; Euis Nurul Hidayah (Yayasan Literasi Sains Indonesia, 2024)
The development of the times will always be accompanied by an increase in population, so infrastructure and a comfortable place to live are needed. However, currently many residential areas are close to public facilities such as stations, highways, airports, and so on. This condition causes noise intensity. Noise intensity can cause health, psychological, communication and productivity problems. Noise is a source of anxiety or pollution, especially in big cities in Indonesia. So, efforts are needed to deal with this. One solution is a natural barrier using Japanese bamboo plants (Pseudosa japonica). Noise measurements are carried out based on the Decree of the Minister of the Environment Number 48 of 1996, namely in a simple way. This research aims to determine the effect of using noise dampening using Japanese bamboo plants and the factors that influence it From the measurements and tests that have been carried out, it is concluded that this barrier can have a significant influence on noise reduction. Noise has little effect on temperature and altitude. The reason is the position of the building is still higher than the position of the bamboo plants which serve as barriers. The highest Ls values ​​are found on Mondays and Saturdays because these 2 days are the start of community activities and the start of holidays. Based on these results, it is necessary to improve the source and arrangement of Japanese bamboo plants according to technical instructions.